2000
DOI: 10.1055/s-2000-13242
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Diabetic Patients with and without an Eating Disorder

Abstract: As part of a multicentre study on the comorbidity of diabetes mellitus and eating disorders, the following paper compares the psychological features of diabetic patients with and without an eating disorder. In a sample of 663 diabetic patients (type 1: n = 341 type 2: n = 322), eating disorder related variables, self-esteem, body acceptance and emotional distress, especially depression in diabetic patients with and without an eating disorder, were compared. A possible relationship to diabetic control was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As insulin is essential for regulating blood sugar levels in individuals with type 1 diabetes, reducing or omitting insulin leads to elevated blood sugar levels, causing the body to break down fat for energy, resulting in weight loss, which may be the desired outcome for some individuals. Several studies have reported that the fear of weight gain is a core component in the emergence of insulin mismanagement [ 64 , 65 ]. However, the act of reducing or omitting insulin can have severe consequences.…”
Section: Diabetes and Disordered Eating Behaviors/eating Disordersmentioning
confidence: 99%
“…As insulin is essential for regulating blood sugar levels in individuals with type 1 diabetes, reducing or omitting insulin leads to elevated blood sugar levels, causing the body to break down fat for energy, resulting in weight loss, which may be the desired outcome for some individuals. Several studies have reported that the fear of weight gain is a core component in the emergence of insulin mismanagement [ 64 , 65 ]. However, the act of reducing or omitting insulin can have severe consequences.…”
Section: Diabetes and Disordered Eating Behaviors/eating Disordersmentioning
confidence: 99%
“…These may include the patient's inability or reluctance to cooperate with the health-care team, affective disorders, cognitive and behavioral disturbances, factitious disease, stress exceeding the patient's coping ability, manipulative attitudes, etc. One should also consider the possibility of insulin omissions (in particular in women and young patients) in order to attain weight loss, disturbed eating behavior and eating disorders (Herpertz et al, 2000).…”
Section: Psychosocial Issues In Diabetes Mellitusmentioning
confidence: 99%